Malaysian geotourism – The Langkawi Geopark as a model area - Mordal, Małgorzata (Geotourism/Geoturystyka, 2015)
The Langkawi Geopark is one of the first geoparks in the region, created under the auspices of UNESCO and can be considered as a role model not only in South East Asia, but also on a global scale. Presently, the approach towards tourism is holistic, therefore, combining the benefits for the environment, local population and tourists (under the idea of sustainable tourism generally and geotourism in particularly) is essential. On the Langkawi Islands, natural conditions for the development of geotourism are outstanding. They exhibit all the major rock types, beginning with those from the Cambrian period, fossil and faults. The most important however, is the fact that all those geological features are well exposed, and they are easy to reach, since the infrastructure on the island is developed excellently. This paper presents the strategy of development of sustainable tourism / geotourism at the governmental level, the geographical settings of Langkawi and geology of Langkawi, infrastructure of Langkawi Geopark and its applied use.